2011
DOI: 10.1158/1078-0432.ccr-11-0642
|View full text |Cite
|
Sign up to set email alerts
|

β1-Integrin: A Potential Therapeutic Target in the Battle against Cancer Recurrence

Abstract: Primary cancer treatment, involving both local and often systemic adjuvant therapy, is often successful, especially if the cancer is detected at an early stage of progression. However, for some patients, the cancer may recur either locally or as distant metastases, in some cases many years after apparently successful primary treatment. Significant tumor dormancy has been documented in several cancers, such as breast, melanoma, and renal cancer. Tumor dormancy has long been recognized as an important problem in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 42 publications
3
116
0
2
Order By: Relevance
“…Recent studies have provided evidence that activation of ␤1 integrin plays a critical role in the release of metastatic tumor cells from dormancy. Three-dimensional culture systems used to model conditions of tumor dormancy have shown that ligation of ␤1 integrins and subsequent organization of the actin cytoskeleton are required for the conversion of quiescent tumor cells into proliferating cells (32)(33)(34). Identifying the mechanisms by which the integrin activation state regulates metastatic cell growth represents an important avenue of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided evidence that activation of ␤1 integrin plays a critical role in the release of metastatic tumor cells from dormancy. Three-dimensional culture systems used to model conditions of tumor dormancy have shown that ligation of ␤1 integrins and subsequent organization of the actin cytoskeleton are required for the conversion of quiescent tumor cells into proliferating cells (32)(33)(34). Identifying the mechanisms by which the integrin activation state regulates metastatic cell growth represents an important avenue of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These three states of existence represent vastly different cancer biology with significant implications for detection, therapy, and patient outcomes. The factors that control the balance between dormancy and proliferation are poorly understood but are subject of much ongoing research [18][19][20][21].…”
Section: Dormancymentioning
confidence: 99%
“…Malignant cells are constantly changing cell adhesion surface molecules in response to signals in their surroundings, and this will enhance their ability to disseminate locally. For these reasons, targeting the interactions between certain cell adhesion apparatuses and the ECM has been proposed, including cell membrane integrins (61,62). Integrin-related mechanisms have been shown to be essential at different stages of EOC progression.…”
Section: Ecm Components and Cell Adhesion Molecules Assist Cancer Migmentioning
confidence: 99%